ROLE OF VIRECHAN KARMA BEFORE KSHARASUTRA PROCEDURE IN THE MANAGEMENT OF BHAGANDARA W.S.R. TO FISTULA IN ANO - M Borkar, Kanchan; V Shekokar, Anantkumar; Mutha, Sonam (International Journal of Ayurveda and Pharma Research, 2015)
Since ages, Bhagandara is the challenge for surgeon. But from three decades Ksharasutra procedure was practised and used with great success without recurrences but it takes long duration to heal. In Ksharasutra procedure patient have pain, foreing body sensation, discomfort and tightness in anal region etc., So to overcome such crucial problems clinical study is required. In ancient ayurvedic texts Bhagandara is Virechan Yogya Vyadhi and advocated Virechan Karma in Bhagandara Chikitsa. So we decided to give Panchtikta Ghrita for Snehan followed Virechan by Aragvadha Hima after that Ksharasutra procedure is done.The present study has been carried out to study the clinical efficacy of Virechan Karma before Ksharasutra procedure in the management of Bhagandara w.s.r.to fistula in ano. A pilot study was conducted, 2 patients selected randomaly and divided into two same group. Group A will be treated with Virechan Karma before Ksharasutra procedure and Group B will be treated with Ksharasutra only. The clinical assessment will be done on the basis of grading criteria. Virechan Karma before Ksharasutra procedure showed better results in reducing pain, itching, burning sensation, pus discharge, unit cutting time and helps in healing of the tract.